1997
DOI: 10.1073/pnas.94.6.2111
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic elite indica rice plants expressing CryIAc ∂-endotoxin of Bacillus thuringiensis are resistant against yellow stem borer ( Scirpophaga incertulas )

Abstract: Generation of insect-resistant, transgenic crop plants by expression of the insecticidal crystal protein (ICP) gene of Bacillus thuringiensis (Bt) is a standard crop improvement approach. In such cases, adequate expression of the most appropriate ICP against the target insect pest of the crop species is desirable. It is also considered advantageous to generate Bt-transgenics with multiple toxin systems to control rapid development of pest resistance to the ICP. Larvae of yellow stem borer (YSB), Scirpophaga in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(84 citation statements)
references
References 34 publications
1
80
0
1
Order By: Relevance
“…Two-dimensional PAGE Analysis of the Receptor Protein-The electroeluted proteins were additionally separated by two-dimensional gel electrophoresis in a Bio-Rad Mini-Protean II Isoelectric focusing unit using carrier ampholytes (3)(4)(5)(6)(7)(8)(9)(10) according to the protocol given by the manufacturer. For the second dimension, gels were run in a MiniProtean III SDS-PAGE module.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional PAGE Analysis of the Receptor Protein-The electroeluted proteins were additionally separated by two-dimensional gel electrophoresis in a Bio-Rad Mini-Protean II Isoelectric focusing unit using carrier ampholytes (3)(4)(5)(6)(7)(8)(9)(10) according to the protocol given by the manufacturer. For the second dimension, gels were run in a MiniProtean III SDS-PAGE module.…”
Section: Methodsmentioning
confidence: 99%
“…Control of aphids using transgenic plants has been suggested as an alternative to pesticide spray. To date, the only commercial insect-resistant transgenic plants are those expressing genes from the soil bacterium Bacillus thuringiensis encoding insecticidal crystal proteins (Bt-toxins) (5)(6)(7)(8)(9)(10). Aphids, including L. erysimi, are not affected by Bt toxins.…”
mentioning
confidence: 99%
“…The most commonly used Bt genes in transgenic crops including rice are Cry1Ab, Cry1Ac, and a fusion gene of Cry1Ac/Cry1Ab or Cry1Ab/c (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, binding tests of midgut brush border membrane vesicles showed that Cry1Aa, Cry1Ab, and Cry1Ac toxins share a common binding site (29)(30)(31); thus, a mutant that is able to overcome one of the Cry1A genes is also likely to be resistant to other Cry1A genes as well.…”
Section: Progresses In Gene Identification and Development Of Gsrmentioning
confidence: 99%
“…There are different reports, in which Bacillus thuringiensis (Bt)-derived genes namely Cry genes have been introduced in rice against insect resistance via different methods of gene delivery electroporation (Fujimoto., 1993), biolistic method (Wunn et al, 1996;Nayak et al, 1997;Ghareyazie 1997;Alam et al, 1998;Datta et al, 1998;Alam et al, 1999); and by Agrobacterium method (Cheng et al, 1998). Fujimoto et al, (1993) were the first to successfully generate the insect-resistant transgenic rice by transferring modified cry1Ab gene from Bacillus thuringiensis.…”
Section: Transgenic Rice For Insect Resistancementioning
confidence: 99%